SEMIOTIK NOVEL LAUT BERCERITA KARYA LEILA SALIKHA CHUDORI - Dani Isma Putra; Fransiska Yelsa F; Saptiana Sulastri; Junius (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the semiotic aspects in the novel Laut Bercerita by Leila Salikha Chudoriusing Charles Sanders Peirce's semiotic theory. The research focuses on identifying and analyzing signs in theform of icons, indices, and symbols in the novel, as well as how these signs represent the profound meaningsembedded within the text. The study employs a qualitative descriptive approach with hermeneutic methods,involving an in-depth analysis of the novel's text and context. The data consists of relevant excerpts from the novel,such as characters, dialogues, and settings, analyzed through a semiotic lens. The findings reveal that icons inthe novel often depict visual and emotional qualities, such as the sound of waves symbolizing resistance. Indiceshighlight causal and existential relationships, such as the physical injuries of characters reflecting trauma.Symbols enrich the narrative, such as the sea, which represents emotional depth and internal conflict. Throughsemiotic analysis, this study successfully unveils the main themes of the novel, including historical trauma,struggle, and hope. This research is expected to contribute to Indonesian literary studies, particularly inunderstanding literary works through a semiotic approach